THE EFFECT OF DANCE THERAPY ON ACADEMIC STRESS - Nugroho , Rizki Wiji; Suroso, Suroso; Muhammad Farid , Muhammad Farid (International Journal of Social and Management Studies, 2023)
School education can determine the quality of life of students in the future and meet some of their needs. However, when teaching, students often experience academic pressure because they cannot adapt to the school curriculum. The Taruna High School program is very good for training discipline, but there is something that needs to be considered because the Taruna High School, one of which is in East Java, uses a competency program, an independent curriculum, and is religiously based, so that the academic load also increases and causes academic stress. This study investigated the effects of dance therapy on academic stress. The type of research used is experimental method research, with a One Group Pretest Posttest Design experimental design . The subjects in this research were Taruna Madani High School students in East Java. The hypothesis proposed is the effect of dance therapy on academic stress. The population used was SMA Taruna Madani East Java students. The research sample consisted of 35 male and female students. The sample was taken using purposive sampling method . The measuring instrument uses the ESSA measuring instrument. Hypothesis testing using the t-test repeated observations obtained a value of t = 12,957 with significance = 0.000 (p <0.05), for the pretest mean (50.00) it decreased during the Posttest (35.36). This shows that there is an effect of dance therapy on academic stress levels after being given dance therapy training, meaning that dance therapy is effective in reducing academic stress.